Epidural Inflammatory Pseudotumor in the Cervical Spine: A Case Report of a Bernese Mountain Dog - Yoshiyuki Inoue; Rie Kitoh; Moe Satoh; Yuki Yoshigae; Kazumi Nibe; Kazuyuki Uchida; Satoru Matsunaga (Animals)
A 3-year, 9-month-old Bernese Mountain dog presented with a 10-day history of acute right hemiparesis. Neurological examination indicated abnormalities in the C1-C5 spinal segments. Magnetic resonance imaging (MRI) revealed an epidural mass at C3-C4, which was surgically removed after dorsal laminectomy. The neurological signs were completely resolved by the 12th postoperative day. The lesion was diagnosed as an inflammatory pseudotumor on histopathological examination. Another MRI performed 63 days after surgery showed no lesion regrowth, and there has been no recurrence for approximately 6 years. Reports of inflammatory pseudotumors are rare, and their treatment remains unclear. Previous reports and the course of this case suggest that a good prognosis may be achieved if complete surgical resection of an inflammatory pseudotumor arising in the epidural region can be accomplished.